2021
DOI: 10.1177/10870547211027650
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Stimulant Misuse in College Students with and Without ADHD

Abstract: In recent years, rates of prescription stimulant misuse have increased among young adults ages 18 to 25 along with increases in dispensing rates of these medications. Preliminary studies suggest that college students with Attention-Deficit Hyperactivity Disorder (ADHD) may be more likely to misuse their stimulant medication than their non-ADHD peers. Research is needed to further explore possible rates, correlates, and outcomes of prescription stimulant misuse among college students with and without ADHD. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…( 2011 ), while Francis et al. ( 2022 ) have also found that symptoms of inattention significantly predicted prescription stimulant misuse in college students with and without a diagnosis of ADHD. This result partially supports the hypothesis that self‐perceived modafinil and methylphenidate users will score significantly higher on the ASRS compared with controls and is consistent with the findings reported by Arria et al.…”
Section: Discussionmentioning
confidence: 99%
“…( 2011 ), while Francis et al. ( 2022 ) have also found that symptoms of inattention significantly predicted prescription stimulant misuse in college students with and without a diagnosis of ADHD. This result partially supports the hypothesis that self‐perceived modafinil and methylphenidate users will score significantly higher on the ASRS compared with controls and is consistent with the findings reported by Arria et al.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription stimulants have a potential for psychological and physiological dependence and are classified by the Drug Enforcement Administration (DEA) as Schedule II medications [6]. Despite the potential health and legal consequences, nonmedical prescription stimulant use (NPSU) remains an ongoing public health concern in the United States [5], [7], [8]. Young adults between the ages of 18 to 25 appear especially vulnerable to nonmedical prescription stimulant use, with prevalence estimates indicating that approximately 7-10% of individuals within this age bracket reported NPSU in 2021 [6].…”
Section: Nonmedical Prescription Stimulant Usementioning
confidence: 99%
“…Prescription stimulants have a potential for psychological and physiological dependence and are classified by the Drug Enforcement Administration (DEA) as Schedule II medications [ 6 ]. Despite the potential health and legal consequences, nonmedical prescription stimulant use (NPSU) remains an ongoing public health concern in the United States [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%